Arsenic and Fluoride Removal by Electrocoagulation Process: A General Review - Salazar-Gonzalez, R; Sandoval, A; Sandoval, A (Elsevier B.V., 2021)
The environmental sector has expressed a growing interest in using electrocoagulation (EC) to treat groundwater/wastewater for drinking/recycling purposes. In the EC process, the electro-dissolution of sacrificial metallic anodes through direct application of current/cell potential dissolves the metals, which precipitate as oxides and hydroxides depending on the electrolyte pH. These particles have large surface areas and can remove pollutants by coagulation. The EC process has been considered an alternative technology due to its versatility, efficiency, low cost, and environmental compatibility. Unfortunately, the lack of knowledge about scaling-up this process has limited its implementation at the industrial scale. The aim of this study is to provide a review of the EC process used for removing arsenic and fluoride from groundwater and wastewater. Approximately 80 published studies were reviewed for this paper. The fundamentals of the EC process and importance of its operating conditions, i.e., electrode material, current density, supporting electrolyte, and pH, are reported in this paper. Additionally, overview of floc characterization and energy consumption are also presented. Finally, this paper also discusses the future perspectives. © 2020 Elsevier B.V.